Toward a Better Understanding of Neuronal Migration Deficits in Autism Spectrum Disorders - Pan, Yi-Hsuan; Wu, Nan; Yuan, Xiao-Bing (Frontiers in Cell and Developmental Biology, 2019)
Newborn neurons in developing brains actively migrate from germinal zones to designated regions before being wired into functional circuits. The motility and trajectory of migrating neurons are regulated by both extracellular factors and intracellular signaling cascades. Defects in the molecular machinery of neuronal migration lead to mis-localization of affected neurons and are considered etiology of multiple developmental disorders including epilepsy, dyslexia, schizophrenia (SCZ), and autism spectrum disorders (ASD). However, the mechanisms that link neuronal migration deficits to the development of these diseases remain elusive. This review focuses on neuronal migration deficits in ASD. From a translational perspective, we discuss (1) whether neuronal migration deficits are general neuropathological characteristics of ASD; (2) how the phenotypic heterogeneity of neuronal migration disorders is generated; (3) how neuronal migration deficits lead to functional defects of brain circuits; and (4) how therapeutic intervention of neuronal migration deficits can be a potential treatment for ASD.